Influence of multiwalled carbon nanotubes content on thermal conductivity of polyactic acid/liquid natural rubber nanocomposite. (8th February 2016) - Tarawneh, Mou'ad A.; Ali, Adilah Mat; Ahmad, Sahrim Hj; Yu, L.J.
Abstract : Purpose: The purpose of this paper is to study the effects of multi-walled carbon nanotubes (MWCNTs) loading on the thermal conductivity of nanocomposites. Design/methodology/approach: In this paper, the polymer nanocomposite of MWCNT nanoparticles incorporated with PLA and LNR as compatibilizer were prepared via melt blending method. Findings: The result has shown that the sample with 3.5 wt.% of MWCNT content provided higher thermal conductivity which is believed to be the optimum loading that formed the suitable percolated network for phonon conduction facilitation because of better dispersion in the PLA/LNR matrix as confirmed by SEM micrograph. Originality/value: Thermal conductivity of polylactic acid (PLA)/liquid natural rubber (LNR) matrix improved with MWCNT.